A theoretical readiness model for 3D printing technology in the architectural construction industry - Silva, Neesha; Rajapaksha, Upendra; Jayasuriya, Chathurika; Katugaha, Rajitha; Udawattha, Chameera (Frontiers in Built Environment, 2026)
This study introduces a tailored theoretical readiness model for evaluating the readiness of the architectural construction industry in developing contexts, with Sri Lanka as a case, to adopt construction 3D printing (C3DP) for custom housing. The unique challenges faced by developing countries underscore the need to address localized contexts and technology adoption dynamics, which distinguishes this model from existing readiness frameworks. The development of this model was initiated through a systematic literature review and bibliometric analysis across five key domains: technological, organizational and environmental, psychological, localized context, and adoption dynamics. A theoretical indicator set was constructed and empirically tested through expert validation, reliability analysis, and factor loading. This process resulted in a 19-component index spanning five key domains, in which technology, organization, and environment emerged as positive indicators and psychology and localized context act as negative influences, with adoption dynamics reflecting both dimensions in relation to C3DP uptake. A practical self-assessment tool was developed to allow stakeholders to measure their preparedness and identify critical gaps. The model provides a structured, context-sensitive framework for guiding strategic decision-making in technology adoption within the construction sector. It offers not only a pathway for assessing readiness in Sri Lanka but also a scalable approach adaptable to other developing economies with similar challenges. The study advances digital construction by aligning theoretical insights with real-world application.